2019
DOI: 10.1371/journal.pone.0224628
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid-stimulated ERK1/2 pathway regulates meiotic initiation in cultured fetal germ cells

Abstract: In murine fetal germ cells, retinoic acid (RA) is an extrinsic cue for meiotic initiation that stimulates transcriptional activation of the Stimulated by retinoic acid gene 8 (Stra8), which is required for entry of germ cells into meiotic prophase I. Canonically, the biological activities of RA are mediated by nuclear RA receptors. Recent studies in somatic cells found that RA noncanonically stimulates intracellular signal transduction pathways to regulate multiple cellular processes. In this study, using a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…Similarly, a positive correlation between ERK1/2 activation and the increased number of cells positive for SYCP3 was observed in mouse testis in a previous study [45], which also demonstrated that Akt-1 inhibition abolished SYCP3 induction and the meiotic entry of postnatal mouse male germ cells [56]. Furthermore, inhibition of ERK1/2 was reported to suppress the genic expression of SYCP3 in cultured fetal germ cells [74]. Therefore, the findings of the present study are evidence for the local regulation of quail spermatogenesis via ERK/Akt-1 activation or inhibition during the reproductive cycle.…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, a positive correlation between ERK1/2 activation and the increased number of cells positive for SYCP3 was observed in mouse testis in a previous study [45], which also demonstrated that Akt-1 inhibition abolished SYCP3 induction and the meiotic entry of postnatal mouse male germ cells [56]. Furthermore, inhibition of ERK1/2 was reported to suppress the genic expression of SYCP3 in cultured fetal germ cells [74]. Therefore, the findings of the present study are evidence for the local regulation of quail spermatogenesis via ERK/Akt-1 activation or inhibition during the reproductive cycle.…”
Section: Discussionsupporting
confidence: 58%
“…(Figures 4A,B and Supplementary Figure 2B), whereas punctate nuclear pERK (pMAPK1/2) was observed in somatic and germ cells of both sexes (Figures 4A,B; control in Supplementary Figure 3A), suggesting some degree of RTK activation in all cells (Figure 4C). The functional significance of the strong cytoplasmic accumulation of total ERK (MAPK1/2) in GONs remains to be further elucidated but could prepare GONs for meiotic entry (after RA signaling) (Kim et al, 2019). In agreement, leptotene/zygotene OGONs show some degree of nuclear ERK/pERK (Figure 4B).…”
Section: Rtk Signaling Ligand-receptor Interactions Between Germ Cells and Gonadal Somatic Cellsmentioning
confidence: 66%
“…ERK1 and ERK2 are required for oocyte maturation (Su et al, 2003;Fan et al, 2009). Moreover, it has been reported that treatment with RA activates ERK1/2 signaling in mouse OGONs (12 dpf) and that this is required to upregulate RA-induced Stra8, a key initiator of meiosis (Kim et al, 2019). The role of ERK activation in C. elegans germ cells has also been linked to meiotic progression, inducing phosphorylation of HTP1 (in human HORMAD1) and SYP-2 (in human SYCEs), which controls the assembly and maintenance of the synaptonemal complex (Nadarajan et al, 2016;Das et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Activated KIT also catalyzes direct phosphorylation of substrate proteins. Among the major signaling pathways ultimately activated by the KL/KIT including RAS-RAF-MEK-ERK, PLCγ, Src, and PI3K/AKT, these two latter are probably the most important to sustain PGC survival and take part in their active migration toward the gonadal anlages [ 22 , 23 , 24 ]. Interestingly, we found that the binding of 17-β-estradiol to its receptor ERα was also able to induce a rapid PI3K-dependent AKT phosphorylation in mouse PGCs [ 25 ].…”
Section: The Pi3k/pten/akt Signaling Pathways In Pgc Developmentmentioning
confidence: 99%
“…In the same paper, a novel role for KL as the PGC chemoattractant and for PI3K/AKT and Src kinase, as players involved in the activation of the PGC migratory machinery, were demonstrated. In addition, evidence for two other possibly PI3K-dependent KL/KIT action on PGCs, adhesion to somatic cells [ 22 ], and survival, this latter, due to a reduction in the expression of the pro-apoptotic Bax gene, have been previously reported [ 23 , 24 ]. Gu’s group [ 15 ] found that the membrane-bound form of KL maintained a high local concentration for mouse PGC motility and defined their region of migration.…”
Section: The Pi3k/pten/akt Signaling Pathways In Pgc Developmentmentioning
confidence: 99%